2015
DOI: 10.1136/ejhpharm-2015-000693
|View full text |Cite
|
Sign up to set email alerts
|

The combination of furosemide and intravenous hydration does not affect the success of shock wave lithotripsy in renal stone treatment: a prospective randomised single blinded trial

Abstract: ObjectivesTo investigate the effect of furosemide given before shock wave lithotripsy (SWL) in patients with renal stones.MethodsTwo-hundred patients with renal stones measuring 6–20 mm in diameter were prospectively included in this study. The treatment group (n=100 patients) received 40 mg furosemide 30 min before SWL plus 1000 mL 0.9% sodium chloride, infused during the procedure. Standard SWL alone was used for the control group (n=100 patients). The effectiveness of SWL was compared between the two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Finally, we included six RCTs that examined the synergistic action of SWL and furosemide against the actions of SWL alone. 9 14 A flowchart of our inclusion/exclusion process is presented in Figure 1 , and the demographics of the six eligible articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we included six RCTs that examined the synergistic action of SWL and furosemide against the actions of SWL alone. 9 14 A flowchart of our inclusion/exclusion process is presented in Figure 1 , and the demographics of the six eligible articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The calculus fragmentation and 3-month SFR were 93.3% and 87.5%, respectively for ESWL with diuresis compared to 70.6% (for fragmentation) for ESWL without diuresis. However, a Turkish single-blinded randomised controlled trial [15], showed that the comparison of the treatment group with the control group had no statistically significant difference in the average number of sessions, number of pulses and total energy used; that is, no benefit was obtained with the additional treatment. In that study the SFR was 71% and 69% in the treatment group and control group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Renal patients are usually in a state of relative dehydration, due to use of purgatives the night before, which improves its effectiveness and fasting until the next day. The dehydration caused by relative oliguria might have a negative effect on stone fragmentation and the fluid film surrounding the stone reportedly enables improved fragmentation of the stone [15]. So, if the treated kidney's function has deteriorated due to the obstruction, the dehydration hinders adequate urine flow around the stone [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the inclusion and exclusion criteria, 6 RCTs [10][11][12][13][14][15] involving 1344 patients were included in the analysis. Table 1 shows the characteristics of the individual RCTs.…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 99%